Three new species of Paronychia (Caryophyllaceae) from Turkey - Budak, Ümi̇t; Hamzaoğlu, Ergi̇n; Coşkunçelebi̇, Kami̇l; Türker, Zeynep (Phytotaxa, 2017)
On the basis of both morphological and molecular data, three new species belonging to the genus Paronychia were described from Turkey: P. aksoyii (from Tortum, Erzurum) which is related to P. saxatilis, P. kocii (from Kelkit, Erzincan) which is related to P. turcica, and P. davrazensis (from Isparta) which is related to P. pontica. Morpholgy, notes on ecology, conservation status and distribution maps are provided for each new species, as well as a morphological comparison with the related taxa is given.